1989
DOI: 10.1073/pnas.86.7.2488
|View full text |Cite
|
Sign up to set email alerts
|

Neural regulation of sex pheromone biosynthesis in Heliothis moths

Abstract: Pheromone biosynthesis in females of Heliothis zea is regulated endogenously by a neuropeptide produced in the subesophageal ganglion. We have found that the ventral nerve cord must be intact for normal induction of pheromone biosynthesis and that pheromonotropic activity is associated with extracts of the abdominal nerve cord, but only during the period when pheromone is produced. We did not find evidence of pheromonotropic activity in hemolymph obtained from females that were producing pheromone. Extracts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 14 publications
1
49
2
Order By: Relevance
“…While this Mating may shut off the release of pheromonotropic peptides, either into the hemolymph or from presumptive release sites in the VNC (19). An intact VNC was previously reported to be essential for pheromone production in H. zea (20); we found, however, that there was no apparent diminution of the pheromone present in the VNC-transected virgins (Fig. 6) (20).…”
Section: Methodscontrasting
confidence: 54%
“…While this Mating may shut off the release of pheromonotropic peptides, either into the hemolymph or from presumptive release sites in the VNC (19). An intact VNC was previously reported to be essential for pheromone production in H. zea (20); we found, however, that there was no apparent diminution of the pheromone present in the VNC-transected virgins (Fig. 6) (20).…”
Section: Methodscontrasting
confidence: 54%
“…Isolated glands (abdominal segments 8 and 9) of H. zea and H. armigera were also stimulated to produce pheromone when incubated with a brain homogenate or with synthetic PBAN (17)(18)(19). However, Teal et al (9) reported that isolated pheromone glands of H. zea were not stimulated by PBAN and presented evidence that intact nerves leading from the TAG are required for PBAN activity. They suggested that a second neurosecretory substance released from the TAG actually stimulated the pheromone gland.…”
Section: Discussionmentioning
confidence: 96%
“…One hypothesis suggests that PBAN is synthesized in the SEG, transported to the corpora cardiaca, and then released into the hemolymph, where it can act on the pheromone gland to induce pheromone biosynthesis (8). The second hypothesis suggests that PBAN is transported from the SEG through the ventral nerve chord (VNC) to the terminal abdominal ganglia (TAG), and then another neurosecretory substance acts on the pheromone gland to induce pheromone production (9). A recent study reported that the pheromone gland is innervated and that the biogenic amine octopamine stimulates pheromone production, suggesting neural regulation of pheromone biosynthesis (10).…”
mentioning
confidence: 99%
“…However, acetate esters can be converted back to the corresponding alcohols through acetate esterase (Figure 1). Teal et al (1989) found significantly higher acetate esterase activity in Hv pheromone glands, suggesting that any acetate esters produced by Hv would be immediately converted back to the corresponding alcohols. Thus, an alternative explanation for the differences between Hv and Hs might involve the presence or activity of acetate esterase.…”
Section: Discussionmentioning
confidence: 87%